Landasan Filosofis dan Substansi Pembaruan dalam Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Bernard Nainggolan (Jurnal Paradigma Hukum Pembangunan, 2016)
The philosophy of foundation form intellectual property rights protection (HKI) include copyrights in. A number of literature refer to and based on “the law theory of nature” (by Aristoteles, Thomas Aquinas, and Hugo Grotius) and “labor theory by John Locke, involved the basic of justifier (legitimate and justify) about why does HKI include in copyrights that needs to be protected. Research of methodology to be used is law octrinal research of methodology with an object research assesment be dedicated against laws regulation which is related to the copyright and the principles of law being valid. Substantially, some materials about changes form UU copyrights contained in UU No. 28 Tahun 2014 that is specially related to the changes in types of criminal from usual crime become complaint, involved penalty and the space protection’s time against copyrights that’s started 50 years ater the creator was died to be 70 years after the creator passed away.